Quantitative synthesis of dynamic combinatorial macrocycles accelerated by preorganization of AIEgens for live visualization of drug release - Yang, Jinghui; Wang, Xin; Wu, Xiaoxia; Lyu, Yonglei; Papageorgiou, Anastassios C.; Li, Jianwei (CELL PRESS, 2025)
In the aggregated state, restricted molecular movement leads to decreased entropy, a phenomenon closely associated with the release of luminescence known as aggregation-induced emission (AIE). This unique optical property is used in optoelectronic devices, biochemical sensors, and bioimaging. Complementing AIE's optical characteristics, we report that AIE-related preorganization can catalyze chemical reactions, yielding highly selective products. These products can affect aggregation states, modulating fluorescence. Incorporating an anticancer drug into this system intensified entropy reduction, accelerated reactions, and altered nanostructure. The drug's electron-donating properties quench fluorescence via energy transfer with the AIE molecule. These components engage in reversible reactions and noncovalent interactions, creating responsive nanosystems for real-time drug release visualization in drug-resistant cancer cells. This synergy between AIE and in situ dynamic covalent reactions offers a promising strategy for synthesizing specific molecules and exploring adaptive nanosystems with advanced optical properties for biomedical applications.